DETERMINANTS OF THE QUALITY OF CARE FOR STUNTED CHILDREN: THE ROLE OF GENDER ROLES, POSYANDU CHECK-UPS, AND HOUSEHOLD CHARACTERISTICS - Apriyanti Latifah, Keukeu; Puspitawati, Herien (Journal of Child, Family, and Consumer Studies, 2025)
In 2021, West Java recorded one of the highest stunting rates in Indonesia, with Garut Regency reporting a prevalence of 35.2 percent among children under five. This public health crisis extends beyond nutritional deficiencies and is exacerbated by suboptimal parenting practices and limited access to basic health services such as posyandu. This study aims to analyze the influence of gender roles in parenting, the frequency of child visits to posyandu, and how parental and child characteristics affect the quality of care for stunted children. A cross-sectional design was applied, involving 40 parents of stunted children in Wanamekar Village, Wanaraja District, using purposive sampling. Data were collected through structured questionnaires and analyzed using Pearson correlation and multiple linear regression. The results revealed significant relationships among gender roles in parenting, health service utilization, and caregiving quality. Regression analysis further demonstrated that child’s birth order, height, parental age, father’s education, mother’s occupation, father’s income, number of household members, child’s health insurance status, and gender-equitable parenting significantly influenced caregiving quality. These findings underscore the importance of integrated, gender-responsive strategies that prioritize equitable parental involvement and access to essential health services. This study offers empirical evidence to support family-centered policy initiatives aimed at improving early childhood development outcomes in resource-limited rural settings.